Sustainability in Library Collection Development - David McCord; Samuel Cassady; Paige Roman; Jacqueline Cato; Elizabeth Mantz (Canadian Journal of Academic Librarianship)
The topic of sustainability generates keen interest in many contemporary spheres. As vital partners in the publishing ecosystem, academic libraries are implicated in the push to make the content that supports teaching and research more equitable and sustainable.  This paper examines the relationship between the practices of academic publishers and the sustainability goals of academic libraries related to collection management, through the lens of a Green Audit featuring a customized rubric to facilitate the assessment of the green practices of publishers.  The research team assessed the environmental practices, current impact, and future commitments of publishers, with an anticipated outcome of reducing their library’s carbon footprint and advancing sustainable collection practices.   Findings are drawn from an audit of sixteen international academic publishers that examined material elements as well as transportation and infrastructure considerations.  Audit results reveal an uneven picture of the industry, owing primarily to funding levels and staffing capacity.